2006
DOI: 10.1128/aem.72.1.596-605.2006
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Bacterial and Fungal Productivity and Carbon Turnover in a Freshwater Marsh

Abstract: Heterotrophic bacteria and fungi are widely recognized as crucial mediators of carbon, nutrient, and energy flow in ecosystems, yet information on their total annual production in benthic habitats is lacking. To assess the significance of annual microbial production in a structurally complex system, we measured production rates of bacteria and fungi over an annual cycle in four aerobic habitats of a littoral freshwater marsh. Production rates of fungi in plant litter were substantial (0.2 to 2.4 mg C g ؊1 C) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
61
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 72 publications
16
61
0
Order By: Relevance
“…A possible explanation is that fungi were relatively inactive at the time when samples were taken 4.5 and 7.5 months after the submergence of the leaf litter in enclosures. This interpretation is in accordance with (i) the relatively low fungal biomass at the time of sampling (for comparison, see reference 21), (ii) declines in fungal biomass observed after the detachment of leaves from emergent macrophyte shoots (as described above), and (iii) the finding that bacterial productivity on submerged plant litter in freshwater marshes appears to assume great importance (9,45). Thus, it is conceivable that at the time of sampling in spring and summer, when leaf litter was in an advanced stage of submerged decomposition, fungi contributed relatively little to the overall activity of the litter-associated microbial communities.…”
Section: Vol 77 2011 Global Change and Microbial Litter Decomposerssupporting
confidence: 71%
See 2 more Smart Citations
“…A possible explanation is that fungi were relatively inactive at the time when samples were taken 4.5 and 7.5 months after the submergence of the leaf litter in enclosures. This interpretation is in accordance with (i) the relatively low fungal biomass at the time of sampling (for comparison, see reference 21), (ii) declines in fungal biomass observed after the detachment of leaves from emergent macrophyte shoots (as described above), and (iii) the finding that bacterial productivity on submerged plant litter in freshwater marshes appears to assume great importance (9,45). Thus, it is conceivable that at the time of sampling in spring and summer, when leaf litter was in an advanced stage of submerged decomposition, fungi contributed relatively little to the overall activity of the litter-associated microbial communities.…”
Section: Vol 77 2011 Global Change and Microbial Litter Decomposerssupporting
confidence: 71%
“…This includes wetlands dominated by emergent aquatic vegetation (21) where plant production often is high (1.5 kg shoot dry mass m Ϫ2 year Ϫ1 or more [23,29]), and only a small fraction is consumed by herbivores (11). In these systems, both bacteria and fungi colonize plant litter and produce a substantial biomass and/or play an important role in the decomposition process (9,21,36,41). The microbial communities colonizing decomposing plant litter can be characterized by means of bulk measures such as total bacterial and fungal biomass and by activity measurements such as respiration, which provide a broad integrative assessment of aerobic microbial metabolism (e.g., see reference 26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carlson et al 2002, Kritzberg et al 2006. Fungal community structure, however, seems to be more dependent on a combination of environmental factors including substrate availability, temperature and competition with bacteria (Buesing & Gessner 2006). The high diversity of obviously different types of fungi on the freshly killed copepods compared to that of decomposing copepod carcasses indicates that even live copepods may have been naturally colonized by presumably parasitic fungi (Carman & Dobbs 1997, Decaestecker et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi play a key role in decomposing leaf litters and other allochthonous detritus in freshwater ecosystems (e.g. Buesing & Gessner 2006), and fungal infection of copepods and their eggs in eutrophic lakes has been frequently observed (Redfield & Vincent 1979, Burns 1980, 1985, but their role in decomposing plankton carcasses has to date not been reported. In a study with the marine copepod Acartia tonsa, Tang et al (2006b) also observed that copepod carcasses were decomposed by unidentified epiphytes in the presence of antibiotics.…”
Section: Discussionmentioning
confidence: 99%